A Critical Appraisal of Lc–Ms/Ms Bioanalytical Method Validation for Cilostazol According To USFDA and ICH M10 - Srushti Chame; Shrikrishna Baokar; Rajendra Patil; Mansingh Rajput (Asian Journal of Pharmaceutical Research and Development, 2026)
Cilostazol is a phosphodiesterase III inhibitor widely used for the treatment of intermittent claudication and prevention of thrombotic events. Accurate quantification of cilostazol in biological matrices is essential for pharmacokinetic evaluation, bioequivalence assessment, and therapeutic monitoring. Liquid chromatography coupled with tandem mass spectrometry has become the gold standard analytical technique due to its superior sensitivity, selectivity, and robustness. Regulatory authorities such as the United States Food and Drug Administration and the International Council for Harmonisation have established comprehensive guidelines to ensure reliability and reproducibility of bioanalytical data. The present review critically evaluates LC–MS/MS bioanalytical method validation for cilostazol with particular emphasis on regulatory expectations outlined in USFDA guidance and ICH M10. Method development strategies, validation parameters, matrix effects, stability considerations, incurred sample reanalysis, data integrity, and lifecycle management are discussed in depth. The article also highlights challenges encountered in real laboratory settings and provides perspectives on harmonization and future trends in bioanalytical science.